1999
DOI: 10.1152/ajpheart.1999.277.2.h474
|View full text |Cite
|
Sign up to set email alerts
|

Human heart failure: cAMP stimulation of SR Ca2+-ATPase activity and phosphorylation level of phospholamban

Abstract: Failing human myocardium has been associated with decreased sarcoplasmic reticulum (SR) Ca2+-ATPase activity. There remains controversy as to whether the regulation of SR Ca2+-ATPase activity is altered in heart failure or whether decreased SR Ca2+-ATPase activity is due to changes in SR Ca2+-ATPase or phospholamban expression. We therefore investigated whether alterations in cAMP-dependent phosphorylation of phospholamban may be responsible for the reduced SR Ca2+-ATPase activity in human heart failure. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 32 publications
5
77
0
2
Order By: Relevance
“…Interestingly, (44 -47). Conversely, in animal models of cardiac disease as well as human patients with heart failure, SERCA2a protein levels and activity often decrease (48,49). Surprisingly, SERCA2a protein levels are increased in the ␣-Tm S283A TG hearts by ϳ30% over NTG levels.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, (44 -47). Conversely, in animal models of cardiac disease as well as human patients with heart failure, SERCA2a protein levels and activity often decrease (48,49). Surprisingly, SERCA2a protein levels are increased in the ␣-Tm S283A TG hearts by ϳ30% over NTG levels.…”
Section: Discussionmentioning
confidence: 98%
“…Limited data exist on the regulation of SERCA2a from human sources, and all data are from explanted hearts at terminal end‐stage HF, that is, a substantially different cohort than the current patients. Notwithstanding this, controversies exist regarding regulation of SERCA2a proteins, where several reports show no change of SERCA2a protein in HF,14, 15, 16, 17, 18, 19, 20 and others show reduced protein levels of SERCA2a 21, 22, 23. Despite the controversies on the extent of SERCA2a protein regulation in human HF, a clinical trial with the aim of increasing the SERCA2a protein levels in patients with HF was designed using recombinant adeno‐associated virus Serotype 1/SERCA2a;24 the initial data from the clinical Phase 1 trial reported promising results,25 but the continued Phase 2b trial failed to improve the clinical course of patients with HF and reduced EF 26.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, in lactotrophs overexpressing HCN2 channels, the overall [Ca 2C ] i was lower compared to non-transfected lactotrophs and an increase in intracellular cAMP did not significantly affect [Ca 2C ] i , 24 consistent with previous results. 26 A possible explanation is that the activation of sarco/endoplasmic reticulum Ca 2C -ATPase (SERCA) 27 decreased global [Ca 2C ] i , as depicted in the model (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%